2014
DOI: 10.1007/s11274-014-1710-4
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of cefdinir by a novel yeast strain, Ustilago sp. SMN03 isolated from pharmaceutical wastewater

Abstract: Cefdinir, a semi-synthetic third generation cephalosporin antibiotic being considered as an emerging pollutant, demands removal from aquatic ecosystems. A yeast strain isolated from pharmaceutical wastewater which was identified as Ustilago sp. SMN03 by molecular techniques and was found to be capable of utilizing cefdinir as a sole carbon source. The isolate was found to degrade 81 % of cefdinir within 6 days under optimized conditions viz. pH 6.0, temperature 30 °C, a shaking speed of 120 rpm, an inoculum do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
1
18
1
Order By: Relevance
“…The results of LC-MS analysis of pure cefdinir (control) and its degradation products are shown in Figure 7 SMN03, where this phenomenal step was observed only on day 4 [30]. This is considered tobe one of the vital steps in the antibiotic degradation process which was also supported by other researchers [19,43,53,54].…”
Section: Liquid Chromatography Tandem Mass Chromatography (Lcms) Is Asupporting
confidence: 67%
See 2 more Smart Citations
“…The results of LC-MS analysis of pure cefdinir (control) and its degradation products are shown in Figure 7 SMN03, where this phenomenal step was observed only on day 4 [30]. This is considered tobe one of the vital steps in the antibiotic degradation process which was also supported by other researchers [19,43,53,54].…”
Section: Liquid Chromatography Tandem Mass Chromatography (Lcms) Is Asupporting
confidence: 67%
“…SMN04 at an initial concentrationof 250 mg L -1 cefdinir. The kinetic rate constant (K) and half-lives (T1/2) and APE% at optimal cefdinir concentration are presented in [30].Therefore, the calculated half-life reported in this study was found to be the shortest compared to the earlier reports.…”
Section: Degradation Kinetics Of Candida Sp Smn04mentioning
confidence: 47%
See 1 more Smart Citation
“…Selvi et al . isolated a kind of fungi named Trametesversicolor which could remove ciprofloxacin and norfloxacin more than 90% 8 . Islas-Espinoza et al .…”
Section: Introductionmentioning
confidence: 99%
“…SMN03, and Candida sp. SMN04 toward cefdinir biodegradation have been reported in our previous studies .…”
Section: Introductionmentioning
confidence: 55%